1998
DOI: 10.1200/jco.1998.16.2.462
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of c-erbB-2 overexpression in primary breast cancer, alone and in combination with other prognostic markers.

Abstract: c-erbB-2 protein overexpression may have a predictive value with regard to adjuvant therapy in node-positive patients, for whom adjuvant tamoxifen with radiotherapy appears insufficient in the presence of c-erbB-2 overexpression. Combination of conventional and newer tumor markers may identify patients with a worse prognosis within groups with a generally favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
162
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(172 citation statements)
references
References 29 publications
6
162
3
1
Order By: Relevance
“…Other groups have also found that overexpression of the HER-2 receptor by patients with breast carcinoma also was predictive of a poor disease prognosis. 13,22,23 Multiple investigators have also found HER-1 overexpression to represent a negative prognosticator for patients with breast carcinoma. 24,25 However, to our knowledge, few groups to date have evaluated the expression of the entire T1GFR family in human breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have also found that overexpression of the HER-2 receptor by patients with breast carcinoma also was predictive of a poor disease prognosis. 13,22,23 Multiple investigators have also found HER-1 overexpression to represent a negative prognosticator for patients with breast carcinoma. 24,25 However, to our knowledge, few groups to date have evaluated the expression of the entire T1GFR family in human breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, amplification of HER2 has also been shown to correlate with resistance to conventional adjuvant chemotherapy and tamoxifen. [6][7][8][9][10] Topoisomerase IIa (TOP2A) gene amplification seems to be predictive of response to a class of cytostatic agents called TopoII inhibitors, which include the anthracyclines. [11][12][13][14][15][16] Recently, estrogen receptor alpha (ESR1) gene amplification has been implicated in response to tamoxifen therapy, 17 but its significance was doubted by others.…”
mentioning
confidence: 99%
“…[2][3][4] Of the total number of patients diagnosed with BC in the United States, 20% to 25% will have tumors that exhibit HER2 gene amplification or protein overexpression. 2,5,6 Trastuzumab (Herceptin), a humanized, monoclonal antibody that blocks the activity of HER2, is the only anti-HER2 agent that is approved for adjuvant therapy in patients who have HER2-positive disease with either positive or negative lymph node status, estrogen receptor (ER)/progesterone receptor (PR)-negative disease, or a high-risk feature, either in combination with chemotherapy or as a single agent after chemotherapy. Adjuvant trastuzumab significantly improves disease-free survival (DFS) and overall survival (OS) compared with chemotherapy or observation alone.…”
mentioning
confidence: 99%